2021
DOI: 10.1021/acsami.1c13119
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli-Responsive Self-Assembly of π-Conjugated Liquids Triggers Circularly Polarized Luminescence

Abstract: We developed novel room-temperature stimuli-responsive N-heteroacene-based liquid materials bearing a chiral alkyl chain. When these liquid materials were exposed to HCl vapor as an external stimulus, a disordered–ordered state change occurred immediately to yield self-assembled solid states from fluidic liquids. The self-assembly mechanism during this state change was evaluated by experimental in situ observations and molecular dynamics simulations over various spatiotemporal scales. These self-assembled stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 55 publications
2
13
0
Order By: Relevance
“…Similarly, compound 3 , which forms a pairing π–π stacking structure, diffuses slower than compound 4 whose π-core is in an isolated environment. In previous studies of other alkyl−π liquids, the phase transition to an ordered phase was observed in which the multilayer π–π stacking grows in chemical stimuli response and a viscosity increase was observed. , Our mechanism can provide a consistent explanation for this as well.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 74%
See 2 more Smart Citations
“…Similarly, compound 3 , which forms a pairing π–π stacking structure, diffuses slower than compound 4 whose π-core is in an isolated environment. In previous studies of other alkyl−π liquids, the phase transition to an ordered phase was observed in which the multilayer π–π stacking grows in chemical stimuli response and a viscosity increase was observed. , Our mechanism can provide a consistent explanation for this as well.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 74%
“…However, atomistic models of the alkyl−π liquids without coarse graining are also necessary to understand the molecular mechanism of the rheology control by changing the substituent positions. Previous theoretical studies based on MD simulations for 1 μs in total showed that the chemical-stimulated phase transition of alkyl−π liquids to an ordered phase where the experimentally measured viscosity significantly increases is attributed to the formation of multilayer π–π stacking columnar structures. , However, the MD analyses were limited to an initial process of the ordered structure formation and static properties of the liquid structures due to short trajectory lengths. We therefore carried out long-time MD simulations for tens of microseconds in total with atomic molecular models and succeeded in semiquantitatively reproducing the rheological properties experimentally observed (Table ).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their remarkable potential applications in changeable photoemission sensors, 3D optical displays, CPL dynamic switching, optical amplifiers, data storage, multiple encryption and anti-counterfeiting, stimuli-responsive circularly polarized luminescent (CPL) materials are attracting widespread attention. [1][2][3][4][5] Currently, a number of stimuli-responsive CPL materials with a high luminescence dissymmetry factor (g lum ) have been favored and fabricated via approaches utilizing the dynamic assembly of liquids, 6 light emitting molecule-binding chiral centers, 7 metal-induced complexes, 8 energy level-assisted photonic inversion, 9 anion-triggered switching, 10 etc. Nevertheless, the fabrication of stimuli-responsive CPL materials with changeable |g lum | and flexible design in the solid state remains a great challenge because of the disorder and aggregation-caused quenching (ACQ) of solid aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…To realize it, one of the most effective methods is doping chiral luminogens into achiral nematic liquid crystals (N-LCs). Besides g lum , another important parameter of CPL is the polarization direction (left-handed and right-handed). Inversion of CPL signals was usually realized by changing the molecular structure or chirality of chiral dopants. It would be more convenient to inverse the CPL signals of N*-LC by simply adjusting the doping ratio of chiral dopants; however, related LC systems were rarely reported.…”
Section: Introductionmentioning
confidence: 99%